Traditional maize post-harvest management practices amongst smallholder farmers in Guatemala. (March 2017) - Mendoza, J.R.; Sabillón, L.; Martinez, W.; Campabadal, C.; Hallen-Adams, H.E.; Bianchini, A.
Abstract: Much of the maize that is produced in Guatemala is planted, harvested and handled via subsistence-oriented agricultural practices, strongly connected to Mayan heritage. This post-harvest assessment study was done to characterize the current practices used in the region of Huehuetenango, Guatemala, in order to identify the different grain handling practices in the region as well as possible factors contributing to post-harvest losses of maize. A total of 280 families representing 14 rural communities were surveyed through interviews. Survey revealed that most (88%) of interviewed farmers prefer to dry the maize cobs after harvest by laying them in stacks exposed to direct sunlight. After drying, harvested maize is stored until consumption along with purchased maize kernels from the market. Among storage practices, 62% of surveyed families store the maize as shelled kernels; while 38% store it on cobs. When storing shelled maize, bags are the preferred containers among 81% of farmers, while only 14% use metal silos. Among farmers who stored maize on cobs, 74% use the tapanco as the preferred storage structure. Forty-one percent of farmers indicated storing the maize for at least 4 months. During the storage time, 61% of farmers perform grain quality checks once a week. Moreover, 65% perform pest control during storage; however, in most cases, the control is not preventive but corrective. For 49% of farmers, the main cause of loss between harvest and consumption is the mishandling of grain moisture, leading to insect and fungal infestation. With this data, it was possible to identify diverse maize harvesting, drying, storage and consumption practices within the studied communities. Understanding the traditional post-harvest practices will help better design intervention steps to improve these practices and to increase food security and food safety for smallholder farmers in the Guatemalan Highlands. Graphical abstract: Highlights: An interview about maize production was carried out in the Highlands of Guatemala. Current traditional pre- and post-harvest practices in Guatemala were identified. Potential causes of postharvest losses in the Highlands of Guatemala. Data will help choose improved post-harvest practices for small farms in Guatemala.